Transient and sustained neuromagnetic representation of consonance and dissonance in harmonic sequences - Schwienbacher, Judith Maria; Rupp, André; Andermann, Martin (Journal of cognitive neuroscience, 2025)
The perception of musical consonance/dissonance (C/D) relies on basic properties of the auditory system, and prior investigations have shown that C/D sounds elicit strongly divergent neurophysiological activity in human auditory cortex. However, studies are missing that assess transient (P1, N1, P2) and sustained cortical C/D representations within a harmonic context, together with the corresponding patterns of neural adaptation. The present magnetoencephalography experiment applied spatio-temporal source analysis to study the early transient and sustained neuromagnetic processing of C/D at the start and within brief harmonic sequences. A total of n = 40 adult listeners (among them numerous amateur musicians) participated in the experiment; the harmonic sequences comprised different blends of C/D dyads with balanced probabilities, in an effort to access simple C/D relations and neural adaptation at an early stage of the processing hierarchy. Consistent with earlier findings, the transient cortical activity was found to reflect vertical (i.e., absolute) C/D aspects in response to the sequence's first dyad, but it mirrored more horizontal aspects (i.e., C/D relations) at the subsequent dyad transitions; moreover, the neuromagnetic responses (particularly, the N1 and P2 waves) exhibited adaptation with different time constants, parts of which pertained to C/D-associated processing. Surprisingly, only few observations appeared to be influenced by the listener's musical expertise, likely due to the high overall level of musicality in our sample. In summary, our data indicate that early neuromagnetic activity reflects not only vertical, but also horizontal, aspects of C/D perception, together with corresponding adaptive mechanisms.
Online verfügbar: 01. Oktober 2025
Gesehen am 16.01.2026